Eye Movement Technique to Improve Executive Function in Patients With Stroke: A Randomized Controlled Trial - He, Wen; Ji, Yazheng; Wei, Xiating; Wang, Fan; Xu, Feng; Lu, Chengyi; Ma, Qianqian; Wang, Kai (Frontiers in Neurology, 2021)
Objective: To investigate the efficacy of eye movement technique for the treatment of executive dysfunction of patients with stroke. Methods:This was a prospective, single-blinded, randomized, controlled, single-center clinical trial conducted from June 2018 to December 2019, for patients with stroke. The patients were randomized 1:1 to theroutine (conventional management) and eye-move group (routine management plus eye movement technique). The intervention lasted 6 weeks, followed by a 4-week follow-up. The primary endpoint was the Behavioral Assessment of the Dysexecutive Syndrome (BADS) score. The secondary endpoints mainly included the Montreal Cognitive Assessment (MoCA), Wisconsin Card Sorting Test (WCST), and modified Barthel Index (MBI) scores. Results: Totally 64 patients were enrolled with 32 in each group. After 6-week intervention,the BADS and WCST scores of the eye-move group were significantly improved than those of the routine group (all P<0.05),but the effects were attenuated in certain subscores after follow-up (allP>0.05). TheMoCA, MBI scores of the eye-move group were significantly higher and the reaction time was significantly lower than those of the routine group after the intervention (all P<0.05). After followup, the MBI scores of the eye-move group were still higher than that of the routine group (P<0.001), but there were no differences for MoCA scores and reaction time(both P>0.05). Conclusion: The eye movement technique could improve the executive function of patients with stroke. Additional studies are necessary to determine the long-term effect of this technique, as well as in a larger sample size.